Is Syringocystadenoma Papilliferum Incidental in This Verrucous Carcinoma? - Tyler Long; Brian Bonomo; Sydney Shearer; William Welton; Ralph Massullo; George Gibbons (Hindawi Limited, 2019)
This case report presents a case in which a collision tumor consisting of three separate pathological entities-a verrucous carcinoma (VC), syringocystadenoma papilliferum (SCAP), and a basal cell carcinoma (BCC). The presentation of this collision tumor is unexpected. It presented as an exophytic mass on the scalp. While collisions of SCAP and VC are present in the literature, this case included an additional pathologic entity. The association of these entities and the unreported location of the lesion may provide some further insight as to the etiology of VC.